Studying the Ingress of Ag Nanoparticles into Imprinted Nanocavities by Nanoimpact Electrochemistry - Hila Sagi-Cohen; Pavel Savchenko; Daniel Mandler (ChemElectroChem)
The significance of nanoimpact electrochemistry (NIE) lies in its simplicity and effectiveness in providing crucial information about the properties of nanoparticles (NPs), such as their sizing. Herein, NIE is applied for the first time to study the ingress of NPs into well‐defined nanocavities. The latter are formed using the NP‐imprinted matrix approach, where Ag NPs adsorbed on a microelectrode are surrounded by an electropolymerized aryldiazonium matrix followed by the anodic dissolution of the NPs. The ingress of Ag NPs into the empty cavities is detected chronoamperometrically by applying a constant voltage microelectrode. It is found that the nanocavities show high selectivity, where only NPs having the same size and capping agents as those used for the imprinting can be detected by NIE. A high match of 84% between the size of the Ag NPs entering the same size of nanocavities is observed for a mixture of two‐sized Ag NPs.